2020
DOI: 10.3390/jcm9051548
|View full text |Cite
|
Sign up to set email alerts
|

Early Predictors of Clinical Deterioration in a Cohort of 239 Patients Hospitalized for Covid-19 Infection in Lombardy, Italy

Abstract: We described features of hospitalized Covid-19 patients and identified predictors of clinical deterioration. We included patients consecutively admitted at Humanitas Research Hospital (Rozzano, Milan, Italy); retrospectively extracted demographic; clinical; laboratory and imaging findings at admission; used survival methods to identify factors associated with clinical deterioration (defined as intensive care unit (ICU) transfer or death), and developed a prognostic index. Overall; we analyzed 239 patients (29.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
160
3
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(184 citation statements)
references
References 41 publications
18
160
3
3
Order By: Relevance
“…The ferritin level was found related to intensive supportive care in patients with diabetes, including ICU transfer (Figure 7A) and treatment with mechanical ventilation, as demonstrated by Herold et al 33 (Figure 7B), which was in accordance with the study of Cecconi et al 70 Ayanian et al also indicated that high levels of ferritin (≥450 ng/mL) were associated with ICU admission (OR 6.8 (95% CI: 3.4‐13.7), intubation (OR 4.0 (95% CI :1.8‐8.8), and death (5.1 (95% CI :2.6‐10.0) 77 . However, our meta‐analysis result showed no significant difference in the ferritin levels between ICU versus non‐ICU subgroup (WMD 683.95 (95% CI −146.25‐1514.15) although they were significant between ICU versus non‐ICU when the patients suffered of diabetes (Figure 7A).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The ferritin level was found related to intensive supportive care in patients with diabetes, including ICU transfer (Figure 7A) and treatment with mechanical ventilation, as demonstrated by Herold et al 33 (Figure 7B), which was in accordance with the study of Cecconi et al 70 Ayanian et al also indicated that high levels of ferritin (≥450 ng/mL) were associated with ICU admission (OR 6.8 (95% CI: 3.4‐13.7), intubation (OR 4.0 (95% CI :1.8‐8.8), and death (5.1 (95% CI :2.6‐10.0) 77 . However, our meta‐analysis result showed no significant difference in the ferritin levels between ICU versus non‐ICU subgroup (WMD 683.95 (95% CI −146.25‐1514.15) although they were significant between ICU versus non‐ICU when the patients suffered of diabetes (Figure 7A).…”
Section: Resultssupporting
confidence: 87%
“…Cecconi et al also revealed that ferritin can aid the early identification and management of patients at risk of clinical deterioration leading to ICU transfer or death in hospitalized COVID‐19 patients 70 . Notably, the changes of ferritin levels in the COVID‐19 patients are not only higher in non‐survivors than in survivors, but also increase with the worsening of the disease 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Some of the enrolled patients have already been involved in other studies evaluating different end points from the current study (20)(21).…”
Section: Methodsmentioning
confidence: 99%
“…Most models use more than one variable and most models predict composite outcomes. Of the 30 models, 23 were trained on patients in China , 2 were trained on patients in the United States 30,31 , and 5 were trained on patients in South Korea 32 or Europe [33][34][35][36] . Only 8 of the models underwent validation on either held-out or external datasets 7,10,14,18,19,24,26,36 , and 1 underwent prospective validation .…”
Section: Introductionmentioning
confidence: 99%